Driving Financial Sustainability Through Organizational Consulting in the ESG Era: Insights from Indonesia - Savandha, Septien Dwi; Abdurokhim, Abdurokhim; Nendi, Ikhsan; Lestari, Anisa Ayu Dwi; Azzahra, Adelia; Zuhriyah, Nabilaa Faizatuz (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objective: This research investigates the role of organizational consulting in promoting financial sustainability by integrating Environmental, Social, and Governance (ESG) principles, with a particular focus on businesses in Indonesia. The study aims to explore how ESG integration can contribute to business growth and rural development in the context of emerging economies.Methodology: A qualitative research approach was employed, utilizing in-depth interviews with organizational consultants and corporate leaders to gather primary data. This was complemented by secondary data analysis from corporate reports and relevant academic literature, providing a comprehensive understanding of the subject.Findings: The findings reveal that ESG integration significantly enhances financial performance, operational efficiency, and investor confidence. Moreover, the adoption of ESG practices contributes to rural development by strengthening local economies and infrastructure. However, challenges such as limited resources, cultural resistance, and a lack of technical expertise impede the widespread adoption of ESG practices, particularly among SMEs. Organizational consulting plays a pivotal role in addressing these challenges through tailored strategies and capacity-building initiatives that support organizations in achieving their sustainability goals.Conclusion: This research underscores the importance of organizational consulting in overcoming barriers to ESG integration, particularly in emerging economies. It emphasizes the need for localized and collaborative approaches to optimize the financial, social, and environmental benefits of sustainability initiatives. The study advances the understanding of ESG integration and offers practical insights for businesses, policymakers, and stakeholders in aligning sustainability goals with financial and social objectives.